Pentingnya Media Pembelajaran dalam Meningkatkan Hasil Belajar di Sekolah Dasar - Lestari, Yulita Dwi (Lentera: Jurnal Ilmiah Kependidikan, 2023)
This study aims to re-analyze the use of learning media to improve science learning outcomes in elementary schools. Meta analysis is used in this research method. In this research begins by looking for a variety of relevant topics in order to facilitate the author in collecting data. The data was obtained by searching online journals through Google Scholar with the keywords SD Learning Media, improving learning outcomes, elementary school science. From the search conducted, 14 articles were obtained, but only the 6 articles that were relevant to use. The data obtained was reprocessed using the quantitative method. Based on the results of the analysis of the use of media in learning, it greatly influences the learning outcomes of students with the lowest result being 43% and the highest being 91%. The use of media in learning greatly influences the learning outcomes of students in learning science. In addition, students also have different experiences in the learning process using media. This can also improve students' ability to understand subject matter easily through the use of media in the learning process.